Challenges in microalgal biofuel production: A perspective on techno economic feasibility under biorefinery stratagem. (January 2022) - Venkata Subhash, G.; Rajvanshi, Meghna; Raja Krishna Kumar, G.; Shankar Sagaram, Uma; Prasad, Venkatesh; Govindachary, Sridharan; Dasgupta, Santanu
Graphical abstract: Rapidly exhausting fossil fuels combined with the ever-increasing demand for energy led to an ongoing search for alternative energy sources to meet the transportation, manufacturing, domestic and other energy demands of the grown population. Microalgae are at the forefront of alternative energy research due to their significant potential as a renewable feedstock for biofuels. However, microalgae platforms have not found a way into industrial-scale bioenergy production due to various technical and economic constraints. The present review provides a detailed overview of the challenges in microalgae production processes for bioenergy purposes with supporting techno-economic assessments related to microalgae cultivation, harvesting and downstream processes required for crude oil or biofuel production. In addition, biorefinery approaches that can valorize the by-products or co-products in microalgae production and enhance the techno-economics of the production process are discussed. Highlights: Prominent challenges associated with microalgae production for bioenergy are discussed. Techno-economic analyses conducted thus far suggest that production of microalgae solely for biofuel is not economically viable. Biorefinery approaches offer valorization of by-products/co-products in microalgae production and hence can improve the overall economics. Experimental data at large scale to establish feasibility of biorefinery approaches is needed. Abstract: Rapidly exhausting fossil fuels combined with the ever-increasing demand for energy led to an ongoing search for alternative energy sources to meet the transportation, manufacturing, domestic and other energy demands of the grown population. Microalgae are at the forefront of alternative energy research due to their significant potential as a renewable feedstock for biofuels. However, microalgae platforms have not found a way into industrial-scale bioenergy production due to various technical and economic constraints. The present review provides a detailed overview of the challenges in microalgae production processes for bioenergy purposes with supporting techno-economic assessments related to microalgae cultivation, harvesting and downstream processes required for crude oil or biofuel production. In addition, biorefinery approaches that can valorize the by-products or co-products in microalgae production and enhance the techno-economics of the production process are discussed.